Anticoagulant Activity of β2-Glycoprotein I Is Potentiated by a Distinct Subgroup of Anticardiolipin Antibodies - Galli, Monica; Comfurius, Paul; Barbui, Tiziano; Zwaal, Robert F A; Bevers, Edouard M (Thrombosis and Haemostasis, 1992)
Plasmas of 16 patients positive for both IgG anticardiolipin (aCL) antibodies and lupus anticoagulant (LA) antibodies were subjected to adsorption with liposomes containing cardiolipin. In 5 of these plasmas both the anticardiolipin and the anticoagulant activities were co-sedimented with the liposomes in a dose-dependent manner, whereas in the remaining cases only the anticardiolipin activity could be removed by the liposomes, leaving the anticoagulant activity (LA) in the supernatant plasma. aCL antibodies purified from the first 5 plasmas were defined as aCL-type A, while the term aCL-type B was used for antibodies in the other 11 plasmas, from which 2 were selected for this study.Prolongation of the dRVVT was produced by affinity-purified aCL-type A antibodies in plasma of human as well as animal (bovine, rat and goat) origin. aCL-type B antibodies were found to be devoid of anticoagulant activity, while the corresponding supernatants containing LA IgG produced prolongation of the dRVVT only in human plasma.These anticoagulant activities of aCL-type A and of LA IgG's were subsequently evaluated in human plasma depleted of β2-glycoprotein I (β2-GPI), a protein which was previously shown to be essential in the binding of aCL antibodies to anionic phospholipids. Prolongation of the dRVVT by aCL-type A antibodies was abolished using β2-GPI deficient plasma, but could be restored upon addition of β2-GPI. In contrast, LA IgG caused prolongation of the dRVVT irrespective of the presence or absence of β2-GPI.Since β2-GPI binds to negatively-charged phospholipids and impedes the conversion of prothrombin by the factor Xa/Va enzyme complex (Nimpf et al., Biochim Biophys Acta 1986; 884: 142–9), comparison was made of the effect of aCL-type A and aCL-type B antibodies on the rate of thrombin formation in the presence and absence of β2-GPI. This was measured in a system containing highly purified coagulation factors Xa, Va and prothrombin and lipid vesicles composed of 20 mole% phosphatidylserine and 80 mole% phosphatidylcholine. No inhibition on the rate of thrombin formation was observed with both types of aCL antibodies when either β2-GPI or the lipid vesicles were omitted. Addition of β2-GPI to the prothrombinase assay in the presence of lipid vesicles causes a time-dependent inhibition which was not affected by the presence of aCL-type B or non-specific IgG. In contrast, the presence of aCL-type A antibodies dramatically increased the anticoagulant effect of β2-GPI. These data indicate that the anticoagulant activity of aCL-type A antibodies in plasma is mediated by β2-GPI.